Virtual Data System on distributed virtual machines in computational grids. (1st October 2010) - Wang, Lizhe; Laszewski, Gregor Von; Tao, Jie; Kunze, Marcel
This paper presents the work of building a Grid workflow system on distributed virtual machines. A Grid Virtualisation Engine (GVE) is implemented to manage virtual machines as computing resources for Grid applications. The Virtual Data System (VDS) functions as a Grid workflow engine. This paper designs and implements the VDS on distributed virtual machines, which are enabled by the GVE. Various interfaces between GVE and VDS have been defined and implemented. A high-energy physics application, the Compact Muon Solenoid (CMS) benchmark, is tested on a test bed equipped with the developed technologies. System discussion, test results and performance evaluation justify the paradigm of building VDS on distributed virtual machines and the prototype of our design and implementation.